Identification of MBW Complex Components Implicated in the Biosynthesis of Flavonoids in Woodland Strawberry - Xu, Pengbo; Wu, Liang; Cao, Minghao; Ma, Chao; Xiao, Kun; Li, Yanbang; Lian, Hongli (Frontiers in Plant Science, 2021)
Flavonoids belong to the family of polyphenolic secondary metabolites and contribute to fruit quality traits. It has been shown that MBW complexes (MYB-bHLH-WD40) regulate the flavonoids biosynthesis in different plants, but only a limited number of MBW complexes have been identified in strawberry species in general. In this study, we identified 112 R2R3-MYB proteins in woodland strawberry; 12 of them were found to have potential functions in regulating flavonoids biosynthesis by phylogenetic analysis. qRT-PCR assays showed that FvMYB3, FvMYB9, FvMYB11, FvMYB22, FvMYB64 and FvMYB105 mostly expressed at green stage of fruit development, aligned with proanthocyanidins accumulation; FvMYB10 and FvMYB41 showed higher expression levels at turning and ripe stages, aligned with anthocyanins accumulation. These results suggest that different MYBs might be involved in flavonoids biosynthesis at specific stages. Furthermore, FvMYB proteins were demonstrated to interact with FvbHLH proteins and induce expression from the promoters of CHS2 and DFR2 genes, which encode key enzymes in flavonoids biosynthesis. The co-expression of FvMYB and FvbHLH proteins in strawberry fruits also promoted the accumulation of proanthocyanidins. These findings confirmed and provided insights into the biofunction of MBW components in the regulation of flavonoid biosynthesis in woodland strawberry.